Social cost of household emissions: cross-country comparison across the economic development spectrum - Yauheniya Shershunovich; Alisher Mirzabaev (Environment, Development and Sustainability, 2023)
AbstractHousehold consumption accounts for the largest share of the global anthropogenic greenhouse gases (GHG) emissions. The literature assessing the environmental impacts of household consumption is mostly focused on developed economies, thus, leaving a critical gap when it comes to assessing the impacts of household consumption and of related environmental policies in developing countries. Therefore, in order to fill this gap, this study analyzes household consumption-based emissions for high income, upper middle income, lower middle income, and low-income countries from six different geographical regions. It assesses the sector-wise CO2, CH4 and N2O-footprints and evaluates their social costs. The study methodology employs an environmentally extended multiregional input–output model from the EORA26 database which uses a common 26-sector classification for all countries. The findings show that household consumption accounts for 48–85% of the national CO2-footprints. (The values are similar for CH4 and N2O.) Developing economies have lower CO2-footprints of household final consumption than developed economies, but exert a higher pressure on the environment with respect to CH4- and N2O-footprints per capita. That highlights the necessity to focus environmental policies in developing countries on tackling CH4 and N2O on a first-priority basis. The study also identifies those sectors where the social costs of aggregated CO2, CH4 and N2O emissions make up a substantial share of the industries' output, thus, indicating the level of technological efficiency of the respective economies and the industries where more stringent environmental regulation should be implemented.
Keywords: 330; Environmentally extended multiregional input–output analysis; Social costs of emissions; Environmental impact of household consumption; Developing countries